The customer-driven organization : employing the kano model - Coleman, Lance B. (Productivity Press, an imprint of Taylor and Francis, 2014)
Does your organization provide customer satisfaction or does it inspire customer loyalty? Which is more important? See how lessons learned from the service sector were applied to manufacturing and other diverse settings, including the nonprofit sector and even on one's own home front. Exploring the Kano Model, The Customer-Driven Organization: Employing the Kano Model explains why just meeting customer needs is no longer enough for today's organizations. It explains how to identify true customers?both internal and external. Readers will learn how to directly apply Kano principles in their own business environments or personal lives, to establish priorities, increase efficiency, improve communication, and expand on existing relationships. The book explains how to establish a value proposition for your organization and, more importantly, how and when to provide "delightful" service. Demonstrating how to incorporate the Kano philosophy into your day-to-day activities, this book is a must-read for any organization or individual looking to do more with less by achieving a truly customer-driven focus.